STUDI KASUS PENERAPAN PUASA INTERMITEN UNTUK MENURUNKAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELITUS: PENERAPAN PUASA INTERMITEN UNTUK MENURUNKAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELITUS - Ari Prayudi; Lucia Firsty Puspita Krishna (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2024)
The number of patients with degenerative diseases such as Diabetes mellitus (DM) is increasing and affects multiple generations within a family. An increase in cases accompanied by inadequate management of blood glucose levels can pose a significant risk of complications and death. One of the non-pharmacological therapies that can be used to lower blood glucose levels is the application of intermittent fasting. Intermittent fasting is a cycle of diet between periods of fasting and eating, while fasting is not allowed to consume liquids that can trigger insulin. The method used is a descriptive method using a nursing process approach with the application of evidence-based practice. Intermittent fasting was carried out for 3 days with a total fasting per day of approximately 16 hours. The results showed a decrease in blood sugar levels to 113 mg/dl which was previously 540 mg/dl. In addition, it is important to conduct education to increase family participation to control blood sugar in family members who experience diabetes mellitus. Keywords : Nursing Care, Diabetes Mellitus (DM), Intermittent Fasting, Family